2011
DOI: 10.1007/s00203-011-0716-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting survival of Listeria monocytogenes and Listeria innocua in soil samples

Abstract: We investigated the ability of several strains of L. monocytogenes and Listeria innocua strains to survive in local soil samples in vitro. Survival of three L. monocytogenes strains, EGDe, CD83, and CD1038, and three L. innocua strains, CLIP, FH2117, FH2152, was monitored in soil samples by direct enumeration of colony-forming units on selective agar. The study did not demonstrate any species-specific difference in soil survival, and all Listeria strains exhibited a marked decline in numbers over time. Biolumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
60
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 35 publications
6
60
1
2
Order By: Relevance
“…The findings of these previous studies may also explain why all of the positive leaf samples in our study were associated with rain events. Additionally, rain events may create favorable conditions for foodborne pathogen growth (e.g., higher soil moisture [55,[58][59][60]), amplifying existing Listeria populations within the field and increasing the likelihood of detection during sampling. Similarly, higher nutrient loads associated with runoff (61-64) could facilitate microbial growth in fields (62,(65)(66)(67).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of these previous studies may also explain why all of the positive leaf samples in our study were associated with rain events. Additionally, rain events may create favorable conditions for foodborne pathogen growth (e.g., higher soil moisture [55,[58][59][60]), amplifying existing Listeria populations within the field and increasing the likelihood of detection during sampling. Similarly, higher nutrient loads associated with runoff (61-64) could facilitate microbial growth in fields (62,(65)(66)(67).…”
Section: Discussionmentioning
confidence: 99%
“…More generally, because the composition and structure of the microbial communities are structured by the complex characteristics of the abiotic environment (43)(44)(45), it is difficult to address the weight of a single parameter on the overall survival of L. monocytogenes in soil. Nevertheless, there is clear evidence that the biotic environment is a key player in the control of the populations of L. monocytogenes, as evidenced by comparisons of population dynamics in microcosms of sterilized and unsterilized soils (9,46,47). Moreover, in a study of experimental ecology, erosion of the soil microbial diversity resulted in the persistence of the population of L. monocytogenes in soil (48).…”
Section: Discussionmentioning
confidence: 99%
“…In Maryland, January 2014 (year 1) and February 2015 (year 2) were the 12th (48) and 6th (49) coldest on record, respectively. Previous research has shown that L. monocytogenes survives better at 5°C than at 15 to 20°C (50,51), and it is able to survive in soil for extended periods at low temperatures (52,53). The persistence of pathogenic Listeria spp.…”
Section: Discussionmentioning
confidence: 99%